Informações sobre gestão estratégica de custos divulgadas por companhias abertas brasileiras - Franciele Wrubel; Carlos Alberto Diehl; Ernani Ott (Revista Contemporânea de Contabilidade, 2010)
This study aimed to identify and analyze information in strategic cost management (GEC), disclosed in the reports for 2005, 2006 and 2007, of Brazilian companies listed in levels of corporate governance (CG) of BOVESPA. Using content analysis of where classifi ed information in 16 categories, based on key themes of Shank and Govindarajan (1997). The average sentence was 212 per company. The amount of disclosure is related to the size of the reports, but not with the size of companies or level of GC. The main difference between the three clusters found is the amount of information disclosed.